1996
DOI: 10.1207/s15327752jpa6602_18
|View full text |Cite
|
Sign up to set email alerts
|

The Splitting Index: Construction of a Scale Measuring the Defense Mechanism of Splitting

Abstract: The Splitting Index (SI), a self-report scale based on the writings of Kernberg (e.g., 1976) on self and object representations and the defense mechanism of splitting, was constructed. After development over the course of 6 pilot studies, the SI was validated through 2 further studies. Factor analyses revealed a 24-item scale with three 8-item subscales, measuring the splitting of self, family, and others' images. The SI and its subscales were demonstrated to be internally consistent and stable over a 4-week p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 0 publications
6
62
0
1
Order By: Relevance
“…The ''Self'' subscale of the ''Splitting Index'' (Gould, Prentice, & Ainslie, 1996). This measure is an 8-item subscale of the Splitting Index (Gould et al, 1996.).…”
Section: Individuation Scalementioning
confidence: 99%
“…The ''Self'' subscale of the ''Splitting Index'' (Gould, Prentice, & Ainslie, 1996). This measure is an 8-item subscale of the Splitting Index (Gould et al, 1996.).…”
Section: Individuation Scalementioning
confidence: 99%
“…The authors found only a weak association (r = .24) of attachment-related anxiety with projective identification and no associations of attachment-related avoidance with any of the defense mechanisms studied. Finally, Lopez (2001) used the ECR to study the association between attachment style and the primitive defense mechanism splitting, measured with the Splitting Index (Gould, Prentice, & Ainslie, 1996). In this study among college students strong associations were found between splitting of self-and other representations and attachment-related anxiety (r = .58 and r = .39, respectively), as well as less strong imposing associations with the attachment-related avoidance (r = .19 and r = .21, respectively).…”
mentioning
confidence: 99%
“…This cognitive immaturity helps maintain psychological cohesion by simplifying attempts to understand instabilities in interpersonal relationships. In the present project, the Splitting Index operationalised Self-Splitting, Family Splitting, and Other Splitting (Gould, Prentice, & Aisnlie, 1996). Two instruments measured tendencies toward the borderline personality (Leichsenring, 1999;Zanarini et al, 2003).…”
Section: Measures Of Religious and Psychological Adjustmentmentioning
confidence: 99%
“…The Splitting Index used eight items each to assess three forms of this defence mechanism (Gould et al, 1996). Exemplifying Self-Splitting (α = .78, M = 2.57, SD = .82) was the statement, "My feelings about myself are very powerful, but they can change from one moment to the next."…”
Section: Splittingmentioning
confidence: 99%